The Role of Scoring Techniques in Improving the Quality of Indonesian Language Learning Evaluation - I Gusti Ayu Mariyati; Ida Bagus Putrayasa (CV. Creative Tugu Pena, 2024)
The article analyzes the role of scoring techniques in improving the quality of Indonesian language learning evaluation. This research uses the library research method. This research aims to describe scoring techniques in language learning. Based on the literature review, scoring techniques play an important role in improving the quality of Indonesian language learning evaluations through the application of objective, valid, and reliable assessment concepts. The conception of scoring techniques emphasizes the importance of clear criteria and standardized assessment methods to measure various aspects of language skills, such as reading, writing, speaking, and listening. Literature studies show that good scoring techniques, such as the use of rubrics and scoring guides, not only ensure accurate assessment results but also support teachers in providing constructive feedback to students. Additionally, the contribution of scoring techniques is evident in their ability to enhance evaluation transparency, assist teachers in designing more targeted teaching strategies, and motivate students to achieve better learning outcomes. Thus, scoring techniques become a strategic element in creating meaningful and high-quality evaluations of Indonesian language learning.